(untitled) (The Spectrum, 2026)
Generative Artificial Intelligence (GenAI), which has been a topic of debate in higher education contexts, has complicated traditional definitions of plagiarism and creativity, for there is no consensus among scholars whether text generated by GenAI is original and/or creative or not. In this paper, we propose rethinking definitions of plagiarism and creativity in the age of GenAI. Our discussion draws on existing conversations about the use and misuse of GenAI and on the changing discourse on plagiarism and creativity in light of GenAI. The discussion shows that there are discontents about the use of GenAI, and the traditional concepts of plagiarism and creativity are potentially challenged. Therefore, drawing on our critical reflections, we propose rethinking plagiarism and creativity in the age of GenAI, positioning GenAI as a collaborator in the learning process. The framework of human-GenAI collaboration not only proposes the ethical use of AI but also aims to invent innovative pedagogical approaches. Hence, this paper not only joins the scholarly conversations about the use of GenAI but also opens avenues for further research.